TEACHER CAPABILITY IN DESIGNING TEACHING MODULES IN LAMPEUNEURUT STATE PRIMARY SCHOOL, ACEH Besar - Paiza, Nur; Sulaiman, Sulaiman; Fauzi, Fauzi (Universitas Syiah Kuala, 2024)
This research aims to describe teachers' abilities in designing teaching modules at the Lampeunerut Elementary School in Aceh Besar. The research method used was direct observation and interviews with teachers involved in the teaching module design process. The data collected includes identification of learning objectives, structure of teaching modules, use of learning resources, consideration of students' needs and learning styles, creativity in designing teaching modules, providing feedback, and efforts to improve teaching modules. The results of the research show that some teachers at the Lampeuneurut Elementary School in Aceh Besar have good abilities in designing teaching modules. Teachers are able to identify learning objectives clearly and organize material in a structured manner. Teachers also use various learning resources, such as textbooks, audio-visual media, and interactive teaching materials. Teachers also consider students' needs and learning styles in designing teaching modules. However, some teachers still need to increase their creativity in designing teaching modules to make them more interesting and interactive. Apart from that, providing feedback to students needs to be improved so that teachers can improve their understanding. Teachers are also advised to continue updating and improving teaching modules based on student feedback and the latest developments in the field of education. This research provides an overview of teachers' abilities in designing teaching modules at the Lampeunerut Elementary School in Aceh Besar. The results of this research can be a reference for teachers to improve teachers' abilities in designing effective teaching modules and supporting students' learning processes.